CONJUNCTIVE RELATION OF GRAMMATICAL COHESION ON FOURTH SEMESTER STUDENTS’ ACADEMIC ESSAY WRITING OF STBA JIA - Elsan Arvian; Imron Hadi (Universitas Wiralodra, 2024)
This research aims to analyze the types of conjunctive relation and the use of all types of each word in academic essay writing of fourth-semester students of STBA JIA. It focuses on 1) identifying the conjunctive item and 2) determining the use of all types of each word of the conjunction of grammatical cohesion on fourth-semester students’ academic essay writing of STBA JIA. The grand theory used for this research is Halliday and Hasan (1976). This research uses a qualitative methodology in which the researcher is knowledgeable about the academic essays, types, and the use of all types of each word of the conjunction of grammatical cohesion. The 20 pieces of data describe the types of conjunctions and show the relation between the use of all types of each word. The percentage of types of conjunction consists of Temporal 74.5%, Adversative 16.3%, Additive 4.1%, and Causal 5.1%. Based on the data, the dominant type of conjunction is Temporal. This research could be further examined and as a reference to assist understanding of conjunctive relation of grammatical cohesion and expected to give some advantages especially for the researcher himself, the respondents, and all university students toward their writing skills.